1957
DOI: 10.1243/pime_proc_1957_171_025_02
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Gear-Tooth Contacts: Some Experiments upon Their Lubrication and Subsurface Deformations

Abstract: This paper describes some experiments with disk machines in which the electrical resistance between the disks was measured at various stages of running. It also describes some experiments with mild steel disks run at such loads that considerable plastic deformation occurred. The resistance measurements illustrate the process of ‘running-in’ and show that a state of almost complete hydrodynamic lubrication is eventually reached. It has also been found that the surface temperatures of the disks have a very cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 5 publications
2
14
0
1
Order By: Relevance
“…3 that the electrical contact voltage signal shows characteristic behaviour similar to that reported by previous workers [2,4,5] in that it oscillates rapidly, and shows intermediate levels between the 43 mV (full film conditions) and 0 mV (high levels of metallic contact) levels. The intermediate contact voltage levels are interesting and may be associated with extremely thin lubricant films having a lower resistance, or light asperity interaction where some form of tribo-film remains on the surface and true metallic contact is not achieved.…”
Section: Superfinished Experiments To Assess Repeatabilitysupporting
confidence: 86%
See 2 more Smart Citations
“…3 that the electrical contact voltage signal shows characteristic behaviour similar to that reported by previous workers [2,4,5] in that it oscillates rapidly, and shows intermediate levels between the 43 mV (full film conditions) and 0 mV (high levels of metallic contact) levels. The intermediate contact voltage levels are interesting and may be associated with extremely thin lubricant films having a lower resistance, or light asperity interaction where some form of tribo-film remains on the surface and true metallic contact is not achieved.…”
Section: Superfinished Experiments To Assess Repeatabilitysupporting
confidence: 86%
“…They found that whilst the variation in contact resistance depended on load in all cases the resistance was the lowest at points of highest sliding, and the highest at the pitch point where there was no relative sliding between the surfaces. Whilst investigating the use of disk machines to simulate gear tooth contacts at particular points within the meshing cycle Crook [4] measured the contact resistance between test disks at various stages of a "running in" process, where he found that initial metal-to-metal asperity contact events were greatly reduced as the surfaces were modified by the running in. Crook also investigated the transient variation of contact resistance, which was found to vary rapidly between high and low levels, a characteristic he attributed to fluctuating levels of asperity interaction within the contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak pressures of the order of 1 GPa or higher are currently encountered, so that not only the elastic limit is passed, but actually also the elastic shakedown and plastic shakedown. Classical experiments on twin-disk rigs such as Crook [1], Merwin [2] (see also [6]), and Hamilton [7], typically used "soft" materials such as copper. This choice was probably suggested to amplify (and therefore make more easily measurements) plastic deformations, but at the same time copper has a quite marked cyclic hardening behaviour and the mechanism of ratchetting in this material is very different from that of rail steel, ultimately more important for railway industry.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on disc machines [8] confirmed that the plastic deformations are inherent in the complex stress cycle involved in rolling and sliding contacts. Two-dimensional plane strain calculations were performed to compute the plastic deformation induced by the translation of a Hertzian pressure distribution and contact area, simulating the passage of a wheel [9][10][11][12].…”
Section: Introductionmentioning
confidence: 81%